Cisplatin nephrotoxicity in male beagle dogs: next-generation protein kidney safety biomarker tissue expression and related changes in urine. Issue 4 (7th June 2016) - McDuffie, J. E.; Chen, Y.; Ma, J. Y.; Lee, S.; Lynch, K. M.; Hamlin, D. M.; Nguyen, L.; Rizzolio, M.; Sonee, M.; Snook, S.
Graphical Abstract: Abstract: This 10-day (D) study was conducted to evaluate changes in traditional and newer kidney safety biomarker expression levels in dogs. Animals received cisplatin (CDDP, 0.75 mg per kg per day) or 0.9% Saline (vehicle) for 5 days. Serum/urine samples were collected at various time points. Cage-side observations included emesis (D1-2/D4-D5/D7-9), absence of stool (D5-9/D11), soft stool (D4-7/D12), excessive salivation (D1/D3/D5-6), decreased food consumption (D5-8), decreased activity (D7-8) and/or dehydration (D7). Animals were necropsied when serum creatinine (sCr) levels measured at ≥1.9 mg dL −1, indicating significant loss of renal function; or at the end of the study (D11). When compared to controls, increases in BUN/sCr were detected on D3, D5 and/or D8. Increases in urinary total protein (Ur TP) were noted on D6. The moribund dog that was euthanized early on D7 showed insignificant increases in urinary osteopontin (Ur OPN), urinary neutrophil gelatinase-associated lipocalin (Ur NGAL), urinary clusterin (Ur CLU), sCr, serum cystatin C (sCYS C) and urinary cystatin C (Ur CYS C) on D5 when compared to controls. Insignificant increases in urinary albumin (Ur ALB) were observed from an animal that was euthanized on D7 and 1 : 2 surviving animals on D8 relative to baseline. From three dogs that were euthanized on D9, increases in Ur CLU, and/or sCYS C were noted on D8 relative to baseline. The two surviving dogs showed elevated Ur CLU and 1 : 2 surviving dogs showed elevated Ur CYS C. Decreased urinary kidney injury molecule 1 (Ur KIM-1) on D3/D5 was evident ( versus baseline and controls). CDDP-induced cortico-medullary lesions were characterized as minimal to mild tubule degeneration/necrosis, dilatation, regeneration, cell alteration, intratubular casts, interstitial inflammation and vacuolization. Increased Ur OPN and Ur CLU correlated with enhanced OPN and CLU immunopositive staining in damaged cortical epithelium in the proximal tubules. Enhanced KIM-1 staining in damaged cortico-medullary tubular epithelium appeared in the absence of rises in Ur KIM-1. This study showed changes in kidney safety protein biomarkers associated with CDDP nephrotoxicity in dogs and possibly in humans.